The Risk of Radiation Exposure to the Eyes of the Interventional Pain Physician - David E. Fish; Andrew Kim; Christopher Ornelas; Sungchan Song; Sanjog Pangarkar (Radiology Research and Practice)
It is widely accepted that the use of medical imaging continues to grow across the globe as does the concern for radiation safety. The danger of lens opacities and cataract formation related to radiation exposure is well documented in the medical literature. However, there continues to be controversy regarding actual dose thresholds of radiation exposure and whether these thresholds are still relevant to cataract formation. Eye safety and the risk involved for the interventional pain physician is not entirely clear. Given the available literature on measured radiation exposure to the interventionist, and the controversy regarding dose thresholds, it is our current recommendation that the interventional pain physician use shielded eyewear. As the breadth of interventional procedures continues to grow, so does the radiation risk to the interventional pain physician. In this paper, we attempt to outline the risk of cataract formation in the scope of practice of an interventional pain physician and describe techniques that may help reduce them.